THE INDUSTRIAL ORGANIZATION MANAGEMENT IN TERMS OF THE DIGITAL ECONOMY - H. Panflova (Вестник университета, 2018)
The article considers the industrial organization management issues in the context of the implementation concept «Industry 4.0». The overview of key production and information technologies, providing a competitive advantage for an industrial or-ganization in the field of digitalization, has given. The necessary conditions for the ef-fective interaction of service and production units within the production company on the base of the Internet of things, additive production and reverse engineering have spec-ified. Methodical recommendations on the organization and control of production pro-cesses, based on the concept of lean production and cross-sectoral cooperation in an in-dustrial organization have given.